A Regularization Method for the Elliptic Equation with Inhomogeneous Source. (4th March 2014) - Nguyen, Tuan H.; Tran, Binh Thanh
Abstract : We consider the following Cauchy problem for the elliptic equation with inhomogeneous source in a rectangular domain with Dirichlet boundary conditions at x = 0 and x = π . The problem is ill-posed. The main aim of this paper is to introduce a regularization method and use it to solve the problem. Some sharp error estimates between the exact solution and its regularization approximation are given and a numerical example shows that the method works effectively.